ONLINE LANGUAGE ASSESSMENT ON SECONDARY SCHOOLS: AN INVESTIGATION ON STUDENTS’ PERCEPTION AND PREFERENCE - Sa'adah, Lailatus; Daning Hentasmaka (E-Link Journal, 2024)
Since the beginning of development, language assessments have been provided on paper. However, since the COVID-19 pandemic, it has shifted from paper-based to online. This phenomenon is still happening even though the pandemic has subsided, considering the advantages revealed. However, did students perceive them well? And did they prefer them as well? This present study aimed to answer those questions using a survey study design. The data were taken from 300 high school students who have carried out online language assessments using e-questionnaire. The questionnaire covered four aspects: ease of access, instruction, benefit, and motivation. Further, the questionnaire clarified students’ preference for the assessment type. Students’ positive perceptions toward language online assessments were found by the descriptive statistics results. They also tended to choose the online assessment over the paper-based one.